School Effectiveness and Inclusion: Cases of Selected Secondary Schools in the Free State, South Africa - Makoelle, Tsediso (International Journal of Educational Sciences, 2014)
The promulgation of the White Paper 6 in 2001 has laid the basis for the implementation of inclusive education in South Africa. However, South Africa has both effective schools which are known of quality teaching and learning and also less effective schools with poor teaching and learning. School effectiveness is mostly thought to be at the heart of effective implementation of educational practices including inclusive education. Therefore this paper examines the relationship between school effectiveness and the extent to which it impacts the practice of inclusion in secondary schools.
Keywords: effective school; effective leadership; inclusive education; Integration; Learner Attainment; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education